2016
DOI: 10.15408/aiq.v9i1.4010
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Approcah for Optimizing of Zakah Institution Performance: Customer Relationship Management

Abstract: Strategic Approach for Optimizing of Zakah Institution Performance: Customer Relationship Management. Zakahh is part of the Indonesian economy, which requires the development and structuring. The funds of zakah must be well managed by organizational zakah system which should be improved its performance. Therefore, there is a need of new approach concerning the zakah management based on muzakki's behavior as an important resource in zakah institution. This paper explores the role of Customer Relationship Manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…By developing potential resources (Spina, Ventura, & Viglianisi, 2016), and using Customer Relationship Management (CRM) (Widarwati, Afif, & Zazim, 2016), as well as management strategies to change mustahiq to muzzaki (Zumrotun, 2016), will support vision and mission, the goals of zakat institutions and policy support from the government regarding zakat as an answer to the challenges of zakat institutions to the Era of Technology (Asminar, 2017).…”
mentioning
confidence: 99%
“…By developing potential resources (Spina, Ventura, & Viglianisi, 2016), and using Customer Relationship Management (CRM) (Widarwati, Afif, & Zazim, 2016), as well as management strategies to change mustahiq to muzzaki (Zumrotun, 2016), will support vision and mission, the goals of zakat institutions and policy support from the government regarding zakat as an answer to the challenges of zakat institutions to the Era of Technology (Asminar, 2017).…”
mentioning
confidence: 99%
“…Thus, according to the result of this study, it can be estimated that at least 3% of GDP should be distributed optimally as Zakah so that the program can be run effectively. Muzaaki seems having different structure of zakah payment (Widarwati et al, 2017) Now we see from the portrait of Indonesian muzaki. Canggih et al (2017) try to estimate the number of Indonesians who are obliged to pay Zakah.…”
Section: Introductionmentioning
confidence: 91%
“…The mustahik's ability to has savings also become one of the components that are measured as points of mutahik's independence in the National Zakah Index (IZN) from BAZNAS (Puskas BAZNAS, 2016a). Muzaaki seems having different structure of zakah payment (Widarwati et al, 2017).…”
Section: Concepts Of Zakahmentioning
confidence: 98%
“…Their research also found that marketoriented fundraising strategies have resulted in greater revenue. Widarwati et al (2017) conclude that there are some principles that can make an optimizing success service of zakah institution: First, the principle of customer, which understanding the customer behavior. Second, the principles of competition, competition is about building brand personal.…”
Section: Zakah Management System In Indonesiamentioning
confidence: 96%